Presentation: After the Incas and Aztecs - Gonzales Alvarado, Osmar (1997)
It is usual to think that between the historical processes of Peru and Mexico there are more similarities than differences. And, indeed, there are reasons to suppose that this is true: both were the cradle of the most developed cultures in the American continent until before the arrival of the Spaniards; later, the two became the most powerful viceroyalties of the Crown; they also followed a similar pattern in their dependent relationship with the international economy; In both territories there is a rich and diverse cultural heritage that, according to some discourses, will merge into a thriving miscegenation. And we could continue with the enumeration.